1970
DOI: 10.1017/s0022377800005067
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic matching of plasma and sheath in an active low pressure discharge

Abstract: The method of matched asymptotic expansions is applied to the fluid model of the low-pressure positive column. The expansion of the eigenvalue in the plasma balance equation is obtained to second order in plane and in cylindrical geometry, and uniformly valid expressions for charged particle densities and fluid velocity in two separate regions are indicated.The free-fall model is also examined and the scales of the transition layer and sheath layer found. Comparison is made with the results of direct numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
158
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(164 citation statements)
references
References 11 publications
6
158
0
Order By: Relevance
“…According to the works of Franklin and Ockendon [2] and Riemann [1], [3]- [5], intermediate scale matching provides an appropriate estimate of the electric field and space charge density at the sheath edge for the hydrodynamic model. For the case the following electric intensity and charge density guesses are good for the range and satisfactory for [5]:…”
Section: Sheath Thickness and Sheath Edge Position Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the works of Franklin and Ockendon [2] and Riemann [1], [3]- [5], intermediate scale matching provides an appropriate estimate of the electric field and space charge density at the sheath edge for the hydrodynamic model. For the case the following electric intensity and charge density guesses are good for the range and satisfactory for [5]:…”
Section: Sheath Thickness and Sheath Edge Position Evaluationmentioning
confidence: 99%
“…Treating this problem as a two-scale problem, Riemann [1], [5] and other early researchers [2]- [4] introduced the intermediate scale matching which has been shown to work well for even more collisional plasmas. In addition, Riemann also showed that the Bohm criterion is the right choice for the sheath boundary only if where is the ion mean free path in presheath region.…”
mentioning
confidence: 99%
“…Such situations arise in sheath problems (see e.g. [16], [18], [11] ; other references can be found in [8]). In such problems, one has often to deal with a dynamic interface the tracking of which gives rise to a complex numerical problem.…”
mentioning
confidence: 99%
“…The purpose of this note is to examine critically the patching process and the developments of it, because that process denies the existence of the region that is necessary to join plasma and collisionless sheath smoothly. Such a region was the natural result of the analyses of the probe-plasma situation given by Lam [2], [3], and for the plasma-wall sheath by Franklin and Ockendon [4]. The analyses referred to, involved the use of the method of matched asymptotic approximations which had by then transformed the field of fluid mechanics and gas dynamics [5].…”
Section: Introductionmentioning
confidence: 99%
“…The analyses referred to, involved the use of the method of matched asymptotic approximations which had by then transformed the field of fluid mechanics and gas dynamics [5]. Its use in plasma physics has been less intensive, but the list of references [2]- [4], [6]- [25], [33], [34], shows that it has been applied in a variety of situations with a significant increase in recent years.…”
Section: Introductionmentioning
confidence: 99%